Derandomization and Local Graph Problems in the Node-Capacitated Clique - Werthmann, Julian

Self-stabilizing Arrow Protocol on Spanning Trees with a Low Diameter - Mengshi, Ma

Guanine condensates as covalent materials and the concept of cryptopores - Kossmann, Janina; Piankova, Diana; V. Tarakina, Nadezda; Heske, Julian Joachim; Kühne, Thomas; Schmidt, Johannes; Antonietti, Markus; López-Salas, Nieves (Carbon)
Simple thermal treatment of guanine at temperatures ranging from 600 to 700 °C leads to C1N1 condensates with unprecedented CO2/N2 selectivity when compared to other carbonaceous solid sorbents. Increasing the surface area of the CN condensates in the presence of ZnCl2 salt melts enhances the amount of CO2 adsorbed while preserving the high selectivity values and C1N1 structure. Results indicate that these new materials show a sorption mechanism a step closer to that of natural CO2 caption proteins and based on metal free structural cryptopores.
Keywords: CN; Cryptopores; Carbon dioxide capture

Immersive augmented reality system for the training of pattern classification control with a myoelectric prosthesis - Boschmann, Alexander; Neuhaus, Dorothee; Vogt, Sarah; Kaltschmidt, Christian; Platzner, Marco; Dosen, Strahinja (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Hand amputation can have a truly debilitating impact on the life of the affected person. A multifunctional myoelectric prosthesis controlled using pattern classification can be used to restore some of the lost motor abilities. However, learning to control an advanced prosthesis can be a challenging task, but virtual and augmented reality (AR) provide means to create an engaging and motivating training. Methods In this study, we present a novel training framework that integrates virtual elements within a real scene (AR) while allowing the view from the first-person perspective. The framework was evaluated in 13 able-bodied subjects and a limb-deficient person divided into intervention (IG) and control (CG) groups. The IG received training by performing simulated clothespin task and both groups conducted a pre- and posttest with a real prosthesis. When training with the AR, the subjects received visual feedback on the generated grasping force. The main outcome measure was the number of pins that were successfully transferred within 20 min (task duration), while the number of dropped and broken pins were also registered. The participants were asked to score the difficulty of the real task (posttest), fun-factor and motivation, as well as the utility of the feedback. Results The performance (median/interquartile range) consistently increased during the training sessions (4/3 to 22/4). While the results were similar for the two groups in the pretest, the performance improved in the posttest only in IG. In addition, the subjects in IG transferred significantly more pins (28/10.5 versus 14.5/11), and dropped (1/2.5 versus 3.5/2) and broke (5/3.8 versus 14.5/9) significantly fewer pins in the posttest compared to CG. The participants in IG assigned (mean ± std) significantly lower scores to the difficulty compared to CG (5.2 ± 1.9 versus 7.1 ± 0.9), and they highly rated the fun factor (8.7 ± 1.3) and usefulness of feedback (8.5 ± 1.7). Conclusion The results demonstrated that the proposed AR system allows for the transfer of skills from the simulated to the real task while providing a positive user experience. The present study demonstrates the effectiveness and flexibility of the proposed AR framework. Importantly, the developed system is open source and available for download and further development.

The Fate of the App: Economic Implications of Updating under Reputation Resetting - Gutt, Dominik; Neumann, Jürgen; Jabr, Wael; Kundisch, Dennis

Algorithms for Distributed Data Structures and Self-Stabilizing Overlay Networks - Feldmann, Michael
This thesis considers the realization of distributed data structures and the construction of distributed protocols for self-stabilizing overlay networks. In the first part of this thesis, we provide distributed protocols for queues, stacks and priority queues that serve the insertion and deletion of elements within a logarithmic amount of rounds. Our protocols respect semantic constraints such as sequential consistency or serializability and the individual semantic constraints given by the type (queue, stack, priority queue) of the data structure. We furthermore provide a protocol that handles joining and leaving nodes. As an important side product, we present a novel protocol solving the distributed $k$-selection problem in a logarithmic amount of rounds, that is, to find the $k$-smallest elements among a polynomial number of elements spread among $n$ nodes. The second part of this thesis is devoted to the construction of protocols for self-stabilizing overlay networks, i.e., distributed protocols that transform an overlay network from any initial (potentially illegitimate) state into a legitimate state in finite time. We present protocols for self-stabilizing generalized De Bruijn graphs, self-stabilizing quadtrees and self-stabilizing supervised skip rings. Each of those protocols comes with unique properties that makes it interesting for certain distributed applications. Generalized De Bruijn networks provide routing within a constant amount of hops, thus serving the interest in networks that require a low latency for requests. The protocol for the quadtree guarantees monotonic searchability as well as a geometric variant of monotonic searchability, making it interesting for wireless networks or applications needed in the area of computational geometry. The supervised skip ring can be used to construct a self-stabilizing publish-subscribe system.

Wiedereinführung der Vermögensteuer – eine ökonomische Analyse - Maiterth, Ralf; Sureth-Sloane, Caren (Steuer und Wirtschaft)
Die Diskussion über die adäquate Besteuerung von „Reichen“ bzw. „Superreichen“ hat durch die Schulden, die im Zusammenhang mit der Coronakrise zu finanzieren sind, neuen Schwung bekommen. Als ein Instrument der adäquaten „Reichenbesteuerung“ gilt eine jährliche Vermögensteuer. Den fiskalischen und verteilungspolitischen Argumenten zugunsten einer Vermögensbesteuerung stehen negative ökonomische Wirkungen entgegen. In diesem Beitrag soll zur Versachlichung der Debatte ein genauerer Blick auf die zu erwartenden Belastungswirkungen einer Vermögensteuer geworfen werden. Dabei wird deutlich, dass die (Wieder-)Einführung der Vermögensteuer nicht nur ungelöste Probleme der Bewertung von Sachvermögen mit sich bringt, sondern die Steuerbelastungswirkungen in der jetzigen Niedrigzinsphase zu erheblichen Nebenwirkungen führen. Berücksichtigt man eine Inflationsrate von 2 %, liegt die zur unternehmerischen Realkapitalerhaltung erforderliche Mindestrendite vor Steuern selbst bei einer lediglich 1 %igen Vermögensteuer mit 5,63 % weit über der Inflationsrate. Dies verdeutlicht, dass eine Vermögensteuer in Zeiten niedriger Renditen für Unternehmen eine zukunftssichernde Eigenkapitalerhaltung oder gar -bildung und zugleich wichtige Investitionen erheblich erschwert. Dies gilt auch für private Anlagen in Aktien und Immobilien. Darüber hinaus ist die Vermögensteuer auch in Verlustperioden zu bezahlen, so dass diese Steuer krisenverschärfend wirkt. Auch dies dürfte erhebliche negative Investitionswirkungen nach sich ziehen. Zudem ist damit zu rechnen, dass die Vermögensteuer zumindest in Teilen überwälzt wird, so dass letztlich auch Verbraucher, Arbeitnehmer und Mieter diese tragen werden. Diese und weitere Nebenwirkungen einer Vermögensteuer kommen in der Vermögensteuerdebatte oftmals zu kurz.

Visualization of dynamic polaronic strain fields in hybrid lead halide perovskites - Guzelturk, Burak; Winkler, Thomas; Van de Goor, Tim W. J.; Smith, Matthew D.; Bourelle, Sean A.; Feldmann, Sascha; Trigo, Mariano; Teitelbaum, Samuel W.; Steinrück, Hans-Georg; de la Pena, Gilberto A.; Alonso-Mori, Roberto; Zhu, Diling; et al. (Nature Materials)

A Review of Existing and Emerging Methods for Lithium Detection and Characterization in Li‐Ion and Li‐Metal Batteries - Paul, Partha P.; McShane, Eric J.; Colclasure, Andrew M.; Balsara, Nitash; Brown, David E.; Cao, Chuntian; Chen, Bor‐Rong; Chinnam, Parameswara R.; Cui, Yi; Dufek, Eric J.; Finegan, Donal P.; Gillard, Samuel; et al. (Advanced Energy Materials)

Modeling cyclic voltammetry during solid electrolyte interphase formation: Baseline scenario of a dynamically evolving tunneling barrier resulting from a homogeneous single-phase insulating film - Steinrück, Hans-Georg (The Journal of Chemical Physics)

Water-in-Salt LiTFSI Aqueous Electrolytes. 1. Liquid Structure from Combined Molecular Dynamics Simulation and Experimental Studies - Zhang, Yong; Lewis, Nicholas H. C.; Mars, Julian; Wan, Gang; Weadock, Nicholas J.; Takacs, Christopher J.; Lukatskaya, Maria R.; Steinrück, Hans-Georg; Toney, Michael F.; Tokmakoff, Andrei; Maginn, Edward J. (The Journal of Physical Chemistry B)

Oligothiophene Phosphonic Acids for Self-Assembled Monolayer Field-Effect Transistors - Zhao, Baolin; Gothe, Bastian; Groh, Arthur; Schmaltz, Thomas; Will, Johannes; Steinrück, Hans-Georg; Unruh, Tobias; Mecking, Stefan; Halik, Marcus (ACS Applied Materials & Interfaces)

Lamellar carbon-aluminosilicate nanocomposites with macroscopic orientation - Paripović, Dragana; Hartmann, Lucia; Steinrück, Hans-Georg; Magerl, Andreas; Li-Destri, Giovanni; Fontana, Yannik; Fontcuberta i Morral, Anna; Oveisi, Emad; Bomal, Enzo; Frauenrath, Holger (Nanoscale)
A liquid-crystalline hexaphenylene amphiphile and an aluminosilicate precursor were co-assembled and pyrolyzed to form carbon-aluminosilicate nanocomposites with controlled lamellar orientation and macroscopic order.

Quantification of heterogeneous, irreversible lithium plating in extreme fast charging of lithium-ion batteries - Paul, Partha P.; Thampy, Vivek; Cao, Chuntian; Steinrück, Hans-Georg; Tanim, Tanvir R.; Dunlop, Alison R.; Dufek, Eric J.; Trask, Stephen E.; Jansen, Andrew N.; Toney, Michael F.; Nelson Weker, Johanna (Energy & Environmental Science)
Realization of extreme fast charging (XFC, ≤15 minutes) of lithium-ion batteries is imperative for the widespread adoption of electric vehicles.

Orientation-Dependent Distortion of Lamellae in a Block Copolymer Electrolyte under DC Polarization - Galluzzo, Michael D.; Grundy, Lorena S.; Takacs, Christopher J.; Cao, Chuntian; Steinrück, Hans-Georg; Fu, Sean; Rivas Valadez, Michael A.; Toney, Michael F.; Balsara, Nitash P. (Macromolecules)

A New Approach to Modeling Leakage Flow in 2 Single-Screw Extrusion - Marschik, Christian; Roland, Wolfgang; Döner, Marius; Steinbichler, Georg; Schöppner, Volker (Polymers)

Joining of ultra-high-strength steels using resistance element welding on conventional resistance spot welding guns - Günter, Heinrich; Meschut, Gerson (Welding in the World)

Managing Multiple Mobile Resources - Feldkord, Björn; Knollmann, Till; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Theory of Computing Systems)

A Nearly Optimal Deterministic Online Algorithm for Non-Metric Facility Location - Bienkowski, Marcin; Feldkord, Björn; Schmidt, Pawel (Proceedings of the 38th Symposium on Theoretical Aspects of Computer Science (STACS))

EUROGRAPHICS 2021: Education Papers Frontmatter